Monitoring and modeling 4-chlorophenol biodegradation kinetics by phenol-acclimated activated sludge by using open respirometry - Lobo, Cintia Cecilia (2018)
The aim of this study was to analyze the mechanisms, stoichiometry, and stability of 4-chlorophenol (4CP) biodegradation kinetics by phenol-acclimated activated sludge using open respirometry. While the removal of 4CP was higher than 98%, the removal of chemical oxygen demand (COD) ranged between 69 and 79% due to the accumulation of an intermediate metabolite. The value obtained from respirometric profiles for the stoichiometric ratio of O 2 to 4CP (Y O2/4CP ) was 1.95 ± 0.04 mol of oxygen consumed per mol of 4CP removed. This Y O2/4CP value reflected the action of the oxygenases responsible for the first steps of the aerobic oxidation of 4CP. The 4CP degradation activity decreased noticeably when successive pulses of 4CP were added to the respirometer. A mathematical model was developed to represent the aerobic biodegradation of 4CP. The fitted model adequately predicted the oxygen consumption rate, total phenols, and soluble COD concentrations as a function of time. The results presented could help to predict the dynamic of biodegradation of chlorophenols in a biological wastewater treatment system.